Autogenous control of Escherichia coli ribosomal protein L10 synthesis in vitro. - Brot, N (1980)
The DNA-dependent in vitro synthesis of Escherichia coli ribosomal protein L10 was inhibited when L10 was added to the protein-synthesizing incubations. Addition of L10 had little or no effect on the synthesis of ribosomal protein L12, elongation factor Tu (tufB), or the beta and beta' subunits of RNA polymerase. In addition, ribosomal protein L12 did not inhibit its own synthesis or the synthesis of L10. Experiments using a mRNA-directed system showed that the inhibition of the synthesis of L10 by itself is at the level of translation of protein synthesis. The mechanism of inhibition does not appear to be due to increased degradation of L10 mRNA.